PENGARUH PROPORSI DAUN PEPAYA (Folium Carica Papaya L.) DAN LIDAH BUAYA (Aloe Berbandesis Miller) TERHADAP UJI KUALITAS FISIK MASKER RAMBUT - Lyva Hidayah Saputri; M.A Hanny Ferry Fernanda; Sri Dwiyanti; Octaverina Kecvara Pritasari (Program Studi Pendidikan Tata Rias, 2026)
This study aims to evaluate the effect of different ratios of papaya leaves (Folium Carica papaya L.) and aloe vera (Aloe barbadensis Miller) on the physical quality of a hair mask, including texture, color, and aroma. The research employed a quantitative method with a pre-experimental design. The hair masks were formulated into three variations of ingredient ratios, namely 1:9, 3:7, and 4:6 of papaya leaves to aloe vera. Physical quality assessment was conducted by 25 semi-trained panelists and 5 trained panelists. The collected data were analyzed using the Friedman test with the assistance of SPSS version 29. The results showed that variations in the proportion of papaya leaves and aloe vera affected the physical quality of the hair mask in terms of texture, color, and aroma. Formula X1 obtained mean scores of 2.77 for texture, 2.87 for color, and 2.47 for aroma. In addition, microbiological testing using the Total Plate Count (TPC) method revealed a microbial count of 3.6 × 10⁴ CFU/ml, or approximately 36,000 colonies/ml. This value is still within safe limits, indicating that hair masks made from papaya leaves and aloe vera have potential to be developed as natural hair care products. Keywords: hair mask, papaya leaves, aloe vera, physical quality, Total Plate Count